Applying Complexity Theory to Interest Rates: Evidence of Critical Transitions in The Euro Area - Jan Willem van den End (Credit and Capital Markets – Kredit und Kapital, 2019)
We apply complexity theory to financial markets to show that excess liquidity created by the Eurosystem has led to critical transitions in the configuration of interest rates. Complexity indicators turn out to be useful signals of tipping points and subsequent regime shifts in interest rates. We find that the critical transitions are related to the increase of excess liquidity in the euro area. These insights can help central banks to strike the right balance between the intention to support the financial system by injecting liquidity and potential unintended side-effects on market functioning. – – Wir wenden Komplexitätstheorie auf Finanzmärkte an, um zu zeigen, dass die vom Eurosystem geschaffene Überschussliquidität zu kritischen Übergängen bei der Konfiguration der Zinssätze geführt hat. Komplexitätsindikatoren erweisen sich als nützliche Signale von Kipppunkten und nachfolgenden Regimeverschiebungen bei Zinssätzen. Wir stellen fest, dass die kritischen Übergänge mit dem Anstieg der Überschussliquidität im Euroraum zusammenhängen. Diese Einblicke können Zentralbanken helfen, das richtige Gleichgewicht zwischen der Absicht, das Finanzsystem mit zusätzlicher Liquidität zu unterstützen, und möglichen unbeabsichtigten Nebenwirkungen auf das Marktgeschehen zu finden.
Keywords: E43; E58; E52; 330; interest rates; central banks and their policies; monetary policy